An augmented reality guide for the “open sky museum” in Valparaíso - Rubio, José Miguel (2011)
The “open sky museum” in Valparaiso, Chile, is an art exposition set in a wide area, over the walls and streets of an emblematic hill of the city. It consists of a series of 20 murals, close to each other, turning the landscape into a space for the promotion of art and culture. However, the picturesque houses, passages and gateways in the hill form an intricate maze that can frustrate im-patient tourists. On the other hand, Augmented Reality (AR) is a technology that is growing as fast as the smartphone market; it uses different sensors of these devices to show a vision of the physical environment combined with virtual information. We develop a navigation guide for the open sky museum that is presented to the user as a layer of augmented reality and can be accessed through the “Layar” publication system. Tourists near the museum can access this guide to see walking paths, location of the artworks, and artist information. In addition, we implement a method to deal with the lack of altitude data on Global Positioning System (GPS) units to correctly display objects with respect to the user altitude.